Boundaryless career drivers - exploring macro-contextual factors in location decisions - Dickmann, Michael; Cerdin, J-L (Cranfield University, 2014)
This paper explores what attracts individuals to live in a South East Asian city. It uses a boundaryless career approach that is interested in how people cross traditional career boundaries, including those related to country and location barriers. Going beyond an individual and organizational view, a more extensive model of location decisions is developed that incorporates broad macro-factor career drivers. "Boundaryless career drivers - exploring macro-contextual factors in location decisions" published in Journal of Global Mobility: The Home of Expatriate Management Research has been selected by the journal's editorial team as the Outstanding Paper of 2014.